Golden dawn - Oldfield, Jenny (Hodder Headline London, 2005)
Kirstie Scott lives, breathes and sleeps horses. She lives with her family at Half Moon Ranch. Undaunted by the wild and dangerous terrain, she loves nothing more than riding through the tall forests and deep canyons of the Meltwater Range ...